Beliefs and practices during pregnancy and childbirth in urban slums of Dhaka, Bangladesh - Chowdhury, Nuzhat; Moran, Allisyn C.; Alam, M Ashraful; Ahsan, Karar Zunaid; Rashid, Sabina Faiz; Streatfield, Peter Kim (© 2012 Choudhury et al.; licensee BioMed Central Ltd., 2017)
This article was published in the BMC Public Health [© 2012 Choudhury et al.; licensee BioMed Central Ltd. ] and the definite version is available at : http://dx.doi.org/10.1186/1471-2458-12-791 The Journal's website is at: http://bmcpublichealth.biomedcentral.com/articles/10.1186/1471-2458-12-791